FAILURE BEHAVIOR OF PARTICULATE-REINFORCED ALUMINUM-ALLOY COMPOSITES UNDER UNIAXIAL TENSION - LEE, JC; SUBRAMANIAN, KN (CHAPMAN HALL LTD, 1992)
Tensile tests were carried out at room temperature on 6061-aluminium alloy reinforced with SiC and Al2O3 particulates. Although a significant increase in strength could be achieved by introducing ceramic reinforcements into the aluminium alloy matrix, it is associated with a substantial decrease in fracture strain. In order to understand the reason for the inferior ductility of such composites, analytical solutions were obtained using a simple composite model. SEM studies were carried out on the side surfaces of the fractured specimens to verify the proposed failure behaviour. Failure modes observed to operate in such composites under uniaxial tension are described.
Keywords: AL-SIC COMPOSITES; METAL MATRIX COMPOSITE; MECHANICAL-PROPERTIES; STRENGTH; DEFORMATION; DUCTILITY; FRACTURE; STRESS